2023
DOI: 10.1021/acsanm.3c01282
|View full text |Cite
|
Sign up to set email alerts
|

Evolution between Volatile and Nonvolatile Resistive Switching Behaviors in Ag/TiOx/CeOy/F-Doped SnO2 Nanostructure-Based Memristor Devices for Information Processing Applications

Abstract: It is well known that higher requirements have been put forward for the computing efficiency and storage speed of the data processing of memory devices in the post Moore era. In particular, if a memory device with multiple physical characteristics can be developed, it will play an important role in realizing multifunctional applications of electronic systems. Here, a nanoscale memristor device with a Ag/TiO x /CeO y /F-doped SnO2 structure was prepared, which shows many interesting physical phenomena with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In recent years, some memristors based on special materials have been discovered to exhibit heightened sensitivity to various external environmental factors, leading to intriguing physical phenomena, including non-zero crossing I-V curves, volatility, non-volatility, negative differential resistance (NDR) effect, and negative photoconductivity (NPD) effect, [30][31][32][33][34][35][36][37][38][39][40][41][42][43] as depicted in Figure 2. These environmental factors include humidity, [32,33] temperature, [34] mechanical stress, [35,36] magnetic field, [41] and light-illumination, [43,44] which can influence the electrical properties of the device by altering the internal structure and the electron mobility of the memristor. The working mechanisms of traditional memristors primarily involve trap/detrap of electrons, thermochemical mechanism (TCM), electrochemical metallization mechanism (ECM), and valence change mechanism (VCM), as shown in Figure 3a-d.…”
Section: Research Hotspotsmentioning
confidence: 99%
“…In recent years, some memristors based on special materials have been discovered to exhibit heightened sensitivity to various external environmental factors, leading to intriguing physical phenomena, including non-zero crossing I-V curves, volatility, non-volatility, negative differential resistance (NDR) effect, and negative photoconductivity (NPD) effect, [30][31][32][33][34][35][36][37][38][39][40][41][42][43] as depicted in Figure 2. These environmental factors include humidity, [32,33] temperature, [34] mechanical stress, [35,36] magnetic field, [41] and light-illumination, [43,44] which can influence the electrical properties of the device by altering the internal structure and the electron mobility of the memristor. The working mechanisms of traditional memristors primarily involve trap/detrap of electrons, thermochemical mechanism (TCM), electrochemical metallization mechanism (ECM), and valence change mechanism (VCM), as shown in Figure 3a-d.…”
Section: Research Hotspotsmentioning
confidence: 99%
“…Zhou et al prepared a photoelectric memristor with two terminal structures based on CeO x /ZnO heterostructure, and tested its recognition, storage, and processing under visible light of 405 nm, indicating that it has great potential applications in artificial vision systems. [33] In addition, Yang et al [34] prepared a memristor device with Ag/TiO x /CeO y /FTO structure, in which it was found that the device shows volatile at low voltage, but it shows nonvolatile memory behavior at high voltage with typical memristive characteristics accompanied by negative differential resistance effect in the range of 3.5-4.0 V. Therefore, in the above works, the performance of the memristive devices has been significantly improved by introducing a double-layer heterostructure due to the interface interaction formed by different material layers.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic behavior of memristors offers a versatile and efficient means for data storage and processing . In a memristor device, a number of different physical effects have been observed, such as volatility, nonvolatility, and the conversion between volatility and nonvolatility characteristics. Nonzero-crossing I–V hysteresis behavior commonly emerges as a result of three fundamental mechanisms: capacitance effect, the formation of internal electromotive force (EMF), and ferroelectric or piezoelectric polarization. , Moreover, the NDR effect can be applied to storage devices, fast switches, , and high-frequency oscillators …”
Section: Introductionmentioning
confidence: 99%